High-Throughput Array Production Using Precision Glass Syringes. (June 2002) - Shieh, J.; To, C.; Carramao, J.; Nishimura, N.; Maruta, Y.; Hashimoto, Y.; Wright, D.; Wu, H.-c.; Azarani, A.
The advantages of using 1, 96, or 384 precision glass syringes in automated high-throughput microdispensers in creating highly uniform and reproducible DNA, protein, and organic compound array filters and slides are described. Using the Hydra ® Microdispenser and Tango TM Liquid Handling system, 0.1–5 ng (in 50–300 nL) PCR-amplified, human cancer-related genes and housekeeping genes were spotted onto nylon membranes and coated slides. Protein solutions of 50 μ g/mL to 1 mg/mL were spotted onto coated slides or onto MaxiSorp TM 96-well plates. Up to 6144 spots/membrane and up to 1000 spots/slide were printed. The size of the spots created by glass syringes was uniform and reproducible (precision variation of less than 5%) from spot to spot and membrane to membrane. Using a Tango 384 system, a total of ten 6144-spot filters can be produced in approximately 25 min, translating into a spotting speed of 2.5 min/membrane.